Novel missense mutation in the ATP1A2 gene associated with atypical sporadic hemiplegic migraine - Rispoli, Marianna Gabriella (BMJ Case Rep, 2019)
Hemiplegic migraine (HM) is a rare subtype of migraine with aura in which attacks include transient motor weakness or hemiparesis that can last several days. HM is linked to mutations in three different genes, CACNA1A, ATP1A2 and SCN1A, which encode for ion transporters. The clinical spectrum includes atypical symptoms such as impaired consciousness, epileptic seizures, permanent cerebellar ataxia or mental retardation. We describe a novel mutation found in the ATP1A2 gene in a patient with late-onset HM. His attacks were characterised by motor weakness associated with altered mental status, diplopia and ataxia. He also showed up MRI abnormalities and incomplete response to prophylactic therapy with verapamil. Late-onset HM should be considered among the possible causes of focal neurological deficits even in older patients with cerebrovascular risk factors when a stroke appears to be more likely.